Exchange rate risk and commodity trade between U.S. and India: an asymmetry analysis. Issue 4 (1st October 2020) - Bahmani-Oskooee, Mohsen; Saha, Sujata
Abstract: Research on the impact of exchange rate volatility on the trade flows has now entered into a new direction of asymmetry analysis. It has been argued by previous researchers, that the rate at which trade flows respond to an increase in volatility could be different than the rate at which they respond to a decrease in volatility, hence asymmetric effects. We consider trade flows of 65 industries that trade between India and the U.S. to show that indeed short-run effects of exchange rate volatility are asymmetric in 58 U.S. exporting industries to India and 55 U.S. importing industries from India. However, short-run effects last into the long run in 45 exporting and 33 importing industries.